PENGARUH TEKNIK MIND MAPPING BERBASIS MODEL PROBLEM BASED LEARNING TERHADAPKETERAMPILANMENULIS KARANGAN NARASI EKSPOSITORIS SISWA KELAS X SMA NEGERI 8 PADANG - Zuraida Zuraida; Dwi Mutia Chan; Najmi Hayati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
The purpose of this research (1) the skills of writing expository narrative essays for class X students of SMA Negeri 8 Padang before applying the mind mapping technique based on problem based learning models.(2) The skills of writing expository narrative essays for class X students of SMA Negeri 8 Padang after applying the mind mapping technique based on problem based learning models.(3) Analyzing the effect of applying mind mapping techniques based on problem based learning models on the skills of writing expository narrative essays for class X students of SMA Negeri 8 Padang. This type of research is quantitative.The research method applied is the experimental method. The research design is a pre-test and post-test group design.The procedure of this research were (1) pretest stage, (2) treatment, (3) posttest.The research sample was 30 class X4 students of SMA Negeri 8 Padang.The instrument used in this study is the performance test.There are three data collection procedures in this study, (1) do a pretest, data collection procedures before applying problem based learning mind mapping techniques,(2) carry out the learning process by applying mind mapping techniques based on problem based learning models,(3) held a posttest. Based on the results of data analysis and discussion, the following conclusions are obtained (1) The skills of writing expository narrative essays for class X4 students of SMA Negeri 8 Padang before being applied to the problem-based learning model-based mind mapping technique were in the "sufficient" qualification with a score of 65.21.(2) The skills of writing expository narrative essays for class X4 students of SMK Negeri 8 Padang after being applied the mind mapping technique based on the problem-based learning model are in the "good" qualification with a score of 81.6.(3) There is an influence of the application of mind mapping techniques based on problem based learning models on the skills of writing expository narrative essays in class X SMA Negeri 8 Padang by testing the hypothesis through measurement using the t-test (t-test) obtained tcount of 4.23, and ttable of 1.70 with a significant level of 0.95 and n-2 degrees of freedom.this means that t count is bigger than t table.Then the research hypothesis is accepted.So, the mind mapping technique based on the problem based learning model is appropriate to be applied in learning to write expository narrative essays for class X students of SMA Negeri 8 Padang.